Modelling the Heating Process in Simultaneous Laser Transmission Welding of Semicrystalline Polymers. (27th October 2016) - Hopmann, Christian; Kreimeier, Suveni
Abstract : Laser transmission welding is an established joining process for thermoplastics. A close-to-reality simulation of the heating process would improve the understanding of the process, facilitate and shorten the process installation, and provide a significant contribution to the computer aided component design. For these reasons a thermal simulation model for simultaneous welding was developed which supports determining the size of the heat affected zone (HAZ). The determination of the intensity profile of the laser beam after the penetration of the laser transparent semicrystalline thermoplastic is decisive for the simulation. For the determination of the intensity profile two measurement systems are presented and compared. The calculated size of the HAZ shows a high concordance to the dimensions of the HAZ found using light microscopy. However, the calculated temperatures exceed the indicated decomposition temperatures of the particular thermoplastics. For the recording of the real temperatures during the welding process a measuring system is presented and discussed.